Immunological Detection of Rabies Virus in Brain Tissues of Infected Dogs by Monoclonal Antibodies - Mantik Astawa, Nyoman; Kade Suardana, Ida Bagus; Agustini, Luh Putu; -, Faiziah (Jurnal Veteriner; Vol 11 No 4 (2010), 2010)
In order to establish an immunological detection of rabies virus in tissues of infected dogs, monoclonalantibodies (mAbs) against rabies virus (RV) were produced. The mAbs were produced by fusion of mielomacells with the lymphocytes of mice immunized with RV. The mAbs produced were then characterized andused for the detection of rabies virus in brain tissues of infected dogs. Six mAbs designated CC6, EG4,DG10, BB12, CA9 dan EB5 were used in this study. In Western blotting test, some mAbs reacted with 66KDa which is the glycoprotein of the virus. In immunoperoxidase, 2 mAbs (CC6 and DG10) detected RVin the brain of infected dogs. By direct immunoflourescence, flourescence isotyocyanate (FITC) labelledDG10 mAbs detected RV in fresh and formaldehyde fixed brain tissues. RV was detected in 12 infecteddogs but not in normal uninfected dogs. In this study it was confirmed that rabies virus can be detected inthe brain tissues of infected dogs by monoclonal antibodies.
Keywords: antibody, monoclonal, brain, rabies, dog